2000
DOI: 10.1021/jp9937961
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and Dynamics of Al Atoms Solvated in Superfluid Helium Nanodroplets

Abstract: The laser-induced fluorescence excitation spectrum in the vicinity of the 32D ← 32P transition of Al atoms solvated in superfluid helium nanodroplets has been measured. While this transition has not been studied in bulk liquid helium, the observed blue shifts and line broadenings, compared with other transitions for which such measurements do exist, allow us to conclude that Al atoms reside in the interior of the helium droplet. The observed transition shows a splitting that we attribute to quadrupole-like def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 35 publications
5
30
0
Order By: Relevance
“…With the fine structure of the 3D state taken into account, this state splits into five M J components. As a consequence the absorption line profile calculated in [59] is composed of five overlapping components and has a spectral shift and a total width close to those of the experimental lineshape from [154]. The authors of [59] also reported a calculation of the absorption spectrum of the 3P − 4S transition that strongly underestimates the blueshift observed in experiment [125].…”
Section: Atomic Fluorescence In Liquid Hementioning
confidence: 54%
See 3 more Smart Citations
“…With the fine structure of the 3D state taken into account, this state splits into five M J components. As a consequence the absorption line profile calculated in [59] is composed of five overlapping components and has a spectral shift and a total width close to those of the experimental lineshape from [154]. The authors of [59] also reported a calculation of the absorption spectrum of the 3P − 4S transition that strongly underestimates the blueshift observed in experiment [125].…”
Section: Atomic Fluorescence In Liquid Hementioning
confidence: 54%
“…In Table 1 we list the elements studied up to date with the corresponding references. Also included in the table are the experiments by [151], [152] and [153,154] on He nano-droplets doped with Ag, Mg and Al atoms, since those atoms reside inside of the droplet and their observed spectra are very similar to those obtained in bulk liquid helium.…”
Section: Atomic Fluorescence In Liquid Hementioning
confidence: 94%
See 2 more Smart Citations
“…Higher temperatures are often used to establish the required vapor pressure from bulk material inside a heated cell. Temperatures exceeding 1500 K have been used in order to evaporate metals [36]. Thermal radiation from the cell or heating are not a problem for the droplet beam because dipole active transitions in helium require 20 eV of photon energy.…”
Section: Doping Of Dropletsmentioning
confidence: 99%